Analisis Kandungan Metabolit Sekunder dan Uji aktivitas Antibakteri Jamur Endofit Batang Binahong (Anredera COrdifiolia Steenis) - Ola, Antonius R B; Bria, Elisabeth Indriyani Paula; da Cunha, Theo (Universitas Nusa Cendana, 2023)
The isolation of endophytic fungi (penicillium sp) from binahong stem had been undertaken with the objective to determine its content of secondary metabolites and its antibacterial activity. The content of secondary metabolites was analyzed with HPLC and its antibacterial activity was measured using paper disc diffusion method. The results showed that there were four compounds in the HPLC chromatogram detected at 235 nm. The antibacterial activity for methanol and ethyl acetate extracts were observed for its diameter of zone inhibition at 18.2 mm and 16.7 mm for S.aureus and 17.8 mm and 16.3 mm for E. Coli.